A novel structured PdZnAl/Cu fiber catalyst for methanol steam reforming in microreactor. (December 2017) - Tian, Jinshu; Ke, Yuzhi; Kong, Guoguo; Tan, Mingwu; Wang, Yong; Lin, Jingdong; Zhou, Wei; Wan, Shaolong
Abstract: Structured PdZnAl/Cu fiber catalyst prepared by a PVA(Polyvinyl Alcohol)-assisted coating method, was integrated in the micro-reactor for methanol steam reforming (MSR), which could be used to efficiently produce hydrogen in situ for a coupled fuel cell. XRD, SEM-EDX and HRTEM etc. were employed to characterize both the fresh and spent powder and structured catalysts. A variety of reaction conditions were tested to achieve the optimized reaction condition, where the H2 productivity and the product distribution especially CO selectivity were carefully examined. Compared to the structured CuZnAlZr/Cu fiber catalyst, the PdZnAl/Cu counterpart exhibits superior stability in MSR process, and its spent catalyst could be readily regenerated just by oxidation in air at 420 °C for 4 h. Highlights: An innovative structured PdZnAl/Cu fiber catalyst was developed. A variety of reaction conditions were tested to achieve the optimized condition. The PdZnAl/Cu fiber catalyst showed good stability for MSR after 72 h test. The deactivation of the PdZnAl/Cu fiber catalyst was reversible.